2015
DOI: 10.1371/journal.pgen.1005683
|View full text |Cite
|
Sign up to set email alerts
|

The Sex Determination Gene transformer Regulates Male-Female Differences in Drosophila Body Size

Abstract: Almost all animals show sex differences in body size. For example, in Drosophila, females are larger than males. Although Drosophila is widely used as a model to study growth, the mechanisms underlying this male-female difference in size remain unclear. Here, we describe a novel role for the sex determination gene transformer (tra) in promoting female body growth. Normally, Tra is expressed only in females. We find that loss of Tra in female larvae decreases body size, while ectopic Tra expression in males inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
158
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(173 citation statements)
references
References 103 publications
15
158
0
Order By: Relevance
“…Overall, these findings suggest that neuronal Sxl promotes female body growth independently of tra , consistent with a longstanding suggestion that SSD regulation is tra -independent [3,4,11]. However, several recent studies have reported that whole body tra mutants do show a reduced female body size when measured either as larval body mass [7] or as pupal volume [15]. This mutant phenotype may be due to cell- or tissue-autonomous effects of Sxl and tra that have been observed in several tissues and appear to operate in addition to the non-autonomous role of Sxl in neurons [8,1517].…”
Section: Sxl Acts In Neurons To Remotely Control Ssd Via a Novel Mechsupporting
confidence: 84%
See 4 more Smart Citations
“…Overall, these findings suggest that neuronal Sxl promotes female body growth independently of tra , consistent with a longstanding suggestion that SSD regulation is tra -independent [3,4,11]. However, several recent studies have reported that whole body tra mutants do show a reduced female body size when measured either as larval body mass [7] or as pupal volume [15]. This mutant phenotype may be due to cell- or tissue-autonomous effects of Sxl and tra that have been observed in several tissues and appear to operate in addition to the non-autonomous role of Sxl in neurons [8,1517].…”
Section: Sxl Acts In Neurons To Remotely Control Ssd Via a Novel Mechsupporting
confidence: 84%
“…This demonstrates that SSD is regulated differently in larval versus imaginal tissue types. It is important to note that we and others [8,15,17,38] have shown that Sxl and Tra have additional cell/tissue-autonomous effects on growth in both tissue types and, in imaginal tissues, these likely explain the gynandromorph observations. Such a combination of cell-autonomous and non-autonomous (hormonal) mechanisms is not restricted to flies and is also important for SSD in mammals [39].…”
Section: Ssd Is Regulated Differently In Larval and Imaginal Tissuesmentioning
confidence: 76%
See 3 more Smart Citations